An Analysis of Authorship and Co-authorship Networks in the Papers of Two Relevant Events in the Brazilian Computing Scenario - Lima, Franklin Matheus da Costa; de Miranda, Leonardo Cunha (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
This work presents the results obtained by an undergraduate student who, throughout their studies, conducted research at the Brazilian Symposium on Human Factors in Computing Systems (IHC), the main national conference in the Human-Computer Interaction field, where bibliometric techniques were applied to investigate this conference scientifically. During the research, a series of studies on IHC were developed, ultimately serving as the foundation for the undergraduate thesis, which analyzed two relevant events in the Brazilian Computing scenario, namely, the IHC itself and the Workshop on Requirements Engineering (WER). The research presented in this work brings several contributions about the achieved results for the two analyzed communities, but especially for the IHC, which was the central point of the research. The methodological contribution of this work is also worth mentioning, as it was the final research challenge. At this stage, the methods of the studies developed for IHC were adapted and applied in the context of WER, demonstrating, therefore, that the methodological foundation built over the years is robust and flexible enough to be used and adapted by other researchers in different contexts.